Melon GliSODin(®) Prevents Diet-Induced NASH Onset by Reducing Fat Synthesis and Improving Liver Function - Nakamura, Anna (Nutrients, 2019)
A high-calorie diet causes fat accumulation and oxidative stress in the liver, leading to fatty liver and eventually non-alcoholic steatohepatitis (NASH). Melon GliSODin(®) is used as a nutritional supplement because of its antioxidant activity. This study aimed to assess the antioxidant activity of Melon GliSODin(®) and its effectiveness in preventing NASH, which primarily results from oxidative stress. Furthermore, we verified the protective effect of Melon GliSODin(®) by administering it to a mouse model of diet-induced NASH. Melon GliSODin(®) suppressed liver fibrosis and fat accumulation, which is characteristic of the NASH phenotype. Gene expression analysis confirmed the suppression of fat synthesis and activation of antioxidative mechanisms. These results show that Melon GliSODin(®) mitigates NASH onset at the molecular level, suggesting its potential application as a NASH preventive agent.